Location Patterns of Manufacturing: Toronto in the Early 1880s - Gad, Gunter (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1994)
The literature on cities simplifies both industrial structure and location patterns of manufacturing in nineteenth-century urban areas, and it conceives of change narrowly in terms of innovations in transportation technology at or after the turn of the century. There are many reasons for rejecting this orthodoxy. Empirical research on Toronto, and other cities, recognizes industries of different scale, capital intensity, labour characteristics, and input-output linkages in the early 1880s. Location patterns for different industries varied from highly centralized ones to those characterized by a great dispersion of factories. There was, however, no straightforward relationship between scale and capital intensity on one hand and location on the other.